Olfactory Function Test for Early Diagnosis of Vascular Dementia - Suh, Kang Duk; Kim, Sun Mi; Han, Doug Hyun; Min, Hyun Jin; Kim, Kyung Soo (Korean journal of family medicine, 2020)
Olfactory impairment occurs in patients with Alzheimer's disease, and olfactory function tests are performed for the diagnosis of Alzheimer's disease. However, the diagnosis and patient status are not currently outlined for vascular dementia, and many physicians do not consider concurrent vascular dementia in patients complaining of olfactory dysfunction. Here, we report a case of vascular dementia with no symptoms of dementia other than olfactory dysfunction. This case suggested that the olfactory function test is helpful not only for the diagnosis of Alzheimer's disease but also for the early diagnosis of vascular dementia.